Explanatory Modelling of Factors Influencing Senior Citizen Telehealth Adoption in COVID-19 Pandemic - Bernardo, Ezekiel; Seva, Rosemary (RSF Conference Series: Business, Management and Social Sciences, 2022)
COVID19 crisis have caused profound changes in our society. A restricted way of living to limit possible widespread contraction has been the new norm. In healthcare, the center of this crisis, the traditional face-to-face consultation is shifting to a technologically backed system of telehealth. The objective of the rollout is to continue to provide basic healthcare service in the convenience and safety of the patients. In the Philippines, this is targeted to prioritize the most vulnerable age group of senior citizen given their needs and implications of quarantine measures. The depth of this transformation, however, is ravaging for senior citizens which are in customary and unfit for this dramatic technology shift. Given this, the objective of the study was to shed light on the significant factor for adoption. To achieve this, the study extended the UTAUT to formulate Health Crisis Technology Adoption Model which incorporates perceived trust and moderated by technological anxiety, resistance to change, and COVID-19 fear. Using Structural Equation Modelling (SEM), the study uncovered that behavioral intention to use telehealth is highly motivated by: low effort needed to use and learn it; support and motivation from important referent; perception of trustworthiness; time reduction and increase in service quality on healthcare as compared to traditional face-to-face checkups; and availability of instructions, trainings, and needed facilities to operate telehealth. The study also determined that COVID-19 fear dampen the conditional barriers or requirements for adoption while technological anxiety and resistance to change amplifies the needed perceived positive benefits from using telehealth.